2019
DOI: 10.3345/kjp.2018.06926
|View full text |Cite
|
Sign up to set email alerts
|

Reninoma: a rare cause of curable hypertension

Abstract: The most common type of refractory hypertension found in children is secondary hypertension, which is a potentially curable disease. Reninoma, a renin-secreting juxtaglomerular cell tumor, is a rare cause of severe hypertension that is usually diagnosed in adolescents and young adults. Surgical resection of the tumor completely cures the hypertension of patients with reninoma. The typical clinical presentation of reninoma includes hypokalemia, metabolic alkalosis, and features secondary to the increased activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Most of the previous case reports have shown that JGCTs located in the cortical or corticomedullary location (5,12,13). However, unlike the renal cell carcinoma, some JGCTs, which were as large as more than 3 cm, could be endophytic entirely in kidney (14)(15)(16). Juxtaglomerular cells are a modified form of the smooth muscle cell, formed from a vascular component of the juxtaglomerular apparatus, and mainly located in the walls of the afferent arterioles (17).…”
Section: Superficial Location Of Jgct and The Pathological Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous case reports have shown that JGCTs located in the cortical or corticomedullary location (5,12,13). However, unlike the renal cell carcinoma, some JGCTs, which were as large as more than 3 cm, could be endophytic entirely in kidney (14)(15)(16). Juxtaglomerular cells are a modified form of the smooth muscle cell, formed from a vascular component of the juxtaglomerular apparatus, and mainly located in the walls of the afferent arterioles (17).…”
Section: Superficial Location Of Jgct and The Pathological Foundationmentioning
confidence: 99%
“…Because of the small size of JGCTs and the popularity of laparoscopic surgery, there is a significantly increased risk of missing JGCTs during surgery. The laparoscopic ultrasound has been applied in previous cases when JGCTs were entire endophytic (14,15). In this study, four JGCTs that were endophytic and indistinguishable in NCCT received the laparoscopic ultrasound.…”
Section: Laparoscopic Partial Nephrectomy Is the Preferred Surgical Strategymentioning
confidence: 99%
“…JGCT is considered as a benign tumor, but one case with pulmonary metastasis was reported. 5 Otherwise, the prognosis is especially related to the consequences of HBP, such as in our case. If no complications occurred, HBP is often asymptomatic, so that screening must systematically be done during any medical consultation.…”
Section: Discussionmentioning
confidence: 68%